Alterations in the retinal vasculature occur in multiple sclerosis and exhibit novel correlations with disability and visual function measures. (June 2020) - Murphy, Olwen C; Kwakyi, Ohemaa; Iftikhar, Mustafa; Zafar, Sidra; Lambe, Jeffrey; Pellegrini, Nicole; Sotirchos, Elias S; Gonzalez-Caldito, Natalia; Ogbuokiri, Esther; Filippatou, Angeliki; Risher, Hunter; Cowley, Norah; et al.
Background: The retinal vasculature may be altered in multiple sclerosis (MS), potentially acting as a biomarker of disease processes. Objective: To compare retinal vascular plexus densities in people with MS (PwMS) and healthy controls (HCs), and examine correlations with visual function and global disability. Methods: In this cross-sectional study, 111 PwMS (201 eyes) and 50 HCs (97 eyes) underwent optical coherence tomography angiography (OCTA). Macular superficial vascular plexus (SVP) and deep vascular plexus (DVP) densities were quantified, and poor quality images were excluded according to an artifact-rating protocol. Results: Mean SVP density was 24.1% (SD = 5.5) in MS eyes (26.0% (SD = 4.7) in non-optic neuritis (ON) eyes vs. 21.7% (SD = 5.5) in ON eyes, p < 0.001), as compared to 29.2% (SD = 3.3) in HC eyes ( p < 0.001 for all MS eyes and multiple sclerosis optic neuritis (MSON) eyes vs. HC eyes, p = 0.03 for MS non-ON eyes vs. HC eyes). DVP density did not differ between groups. In PwMS, lower SVP density was associated with higher levels of disability (expanded disability status scale (EDSS): R 2 = 0.26, p = 0.004; multiple sclerosis functional composite (MSFC): R 2 = 0.27, p = 0.03) and lower letter acuity scores (100% contrast: R 2 = 0.29; 2.5% contrast: R 2 = 0.40; 1.25% contrast: R 2 = 0.31; p < 0.001 for all). Conclusions: Retinal SVP density measured by OCTA is reduced across MS eyes, and correlates with visual function, EDSS, and MSFC scores.